2020
DOI: 10.3389/fnins.2020.577958
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Zinc Excitotoxicity: A Focus on AMPK

Abstract: Over the last 20 years, it has been shown that complex signaling cascades are involved in zinc excitotoxicity. Free zinc rapidly induces PKC activation, which causes reactive oxygen species (ROS) production at least in part through NADPH oxidase. It also promotes neuronal nitric oxide synthase, thereby increasing nitric oxide (NO) production. Extracellular signal-regulated kinase activation and Egr-1 transcription factor activity were quickly induced by zinc, too. These concurrent actions of kinases consequent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 96 publications
1
16
0
Order By: Relevance
“…At the same time, Manev et al, (1997) found that amlodipine ameliorated both mitochondrial injury and cell death in zinc neurotoxicity in rat cerebellar granule cells. It is declared that Zn 2+ induce neuronal death by enhancing glutamate excitotoxicity (Kim et al, 2020). Specifically, our results show that similar to previous reports lacidipine and amlodipine alleviated glutamate-induced excitotoxicity in neuron and SH-SY5Y cells in a concentration-dependent.…”
Section: Discussionsupporting
confidence: 91%
“…At the same time, Manev et al, (1997) found that amlodipine ameliorated both mitochondrial injury and cell death in zinc neurotoxicity in rat cerebellar granule cells. It is declared that Zn 2+ induce neuronal death by enhancing glutamate excitotoxicity (Kim et al, 2020). Specifically, our results show that similar to previous reports lacidipine and amlodipine alleviated glutamate-induced excitotoxicity in neuron and SH-SY5Y cells in a concentration-dependent.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, enhanced cytoprotective autophagy can mitigate glutamate-induced excitotoxicity. We may have long overlooked that other cations, such as zinc ions, may play an essential role in AMPK-mediated excitotoxicity ( Granzotto et al, 2020 ; Kim et al, 2020 ). New ion-tracing techniques, such as ultrahigh-resolution optical microscopy, are promising approaches that can be used to unravel these mysteries ( Chen Q. et al, 2020 ; Fang et al, 2021 ; Wang L. et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Glutamate is the major excitatory neurotransmitter in the central nervous system and it is essential for cognition and emotion ( 51 ). Also, glutamate excitotoxicity has been shown to be partially mediated by zinc overload in the postsynaptic neuron ( 52 ). Thus, a putative adaptive function of Met50Val substitution to reduce zinc-mediated excitotoxicity is an attractive hypothesis that deserves further studies.…”
Section: Discussionmentioning
confidence: 99%